Monomethacrylate derivative of ED-24 epoxy resin and its application - Iatsyshyn, Oksana; Astakhova, Olena; Shyshchak, Olena; Lazorko, Olexander; Bratychak, Michael (Lviv Polytechnic Publishing House, 2013)
Resin derivative containing methacrylic fragment and free epoxy group at the same time has been synthesized via chemical modification of ED-24 epoxy dianic resin by methacrylic acid. The structure of the synthesized product has been confirmed by IRspectroscopic investigations. Derivatography was used to determine the thermal stability of the synthesized compound. It has been suggested to use methacrylate derivative of ED-24 epoxy resin as a component of epoxyoligoesteric and bitumen-polymeric mixtures. Хімічною модифікацією епоксидної діанової смоли ЕД-24 метакриловою кислотою синтезована похідна смоли, що містить одночасно метакриловий фрагмент та вільну епоксидну групу. Структура синтезованого продукту підтверджена ІЧ-спектроскопічними дослідженнями. Дериватографічними дослідженнями встановлена термічна стабільність синтезованої сполуки. Запропановано використовувати метакрилатну похідну епоксидної смоли ЕД-24 як компонент епокси-олігоестерних та бітум-полімерних сумішей.
Монометакрилатна похідна епоксидної смоли ЕД-24 та її застосування
Keywords: epoxy resin; methacrylic acid; chemical modification; IR-study; derivatography; epoxy-oligomeric and bitumen-polymeric mixture; group analysis; епоксидна смола; метакрилова кислота; хімічна модифікація; ІЧ-спектроскопія; дериватографічні дослідження; епокси-олігомерні та бітум-полімерні суміші; структурно-груповий аналіз бітумів